Psychophysical and Social Development of Persons with Down Syndrome - Kovtun, R. A. (Psychological Prospects Journal, 2011)
In the article pshycophisical and social developments of persons with the Daun Syndrome are revealed. The primary attention is focused on practical actions for providing the corretional orientation of studies, comprehensive development of children, with the Daun Syndrome, since implementation of action will help to concentrate interest on the object more long time, sending activity in a necessary direction.